A selected bibliography of periodical articles on the music of the native peoples of Sub-Saharan Africa - Thieme, Darius L. (International Library of African Music, 1962)
The present work was motivated primarily by the writer's own interest in African studies- in particular, in the music of sub-Saharan Africa. There has been a widespread awakening of interest in all aspects of African studies in recent times. The prime catalysts, of course, are the emerging nations of Africa. Together with this interest, there is a continuing awareness on the part of scholars of the value of the interdisciplinary approach in studying the complex cultures of Africa, i.e., of bringing several different points of view to bear upon the study of a particular culture, for the purpose of attaining a more complete picture of the culture as a whole. The writer thus hopes that the present work will be of use not only to students of African music, but also to Africanists in other fields seeking to broaden their knowledge and understanding of this vast area and its various peoples.
Keywords: Music; Bibliography; Africa; Ethnology; Sub-Saharan Africa; African Music